Nematodes parasitic in fishes of cenotes (= sinkholes) of the Peninsula of Yucatan, Mexico. Part 2. Larvae - Moravec, František; Vivas-Rodríguez, C; Scholz, T; Vargas-Vázquez, J; Mendoza-Franco, E; Schmitter-Soto, J J; González-Solís, D (Folia parasitologica, 1995)
This paper comprises a systematic survey of larval nematodes collected from fishes from cenotes (= sinkholes) of the Peninsula of Yucatan, southern Mexico, in 1993-1994. Larvae of the following nine species were recorded: Physocephalus sexalatus, Acuariidae gen. sp., Spiroxys sp., Falcaustra sp., Hysterothylacium cenotae, Contracaecum sp. Type 1, Contracaecum sp. Type 2, Goezia sp., and Eustrongylides sp. Larvae of P. sexalatus are recorded from fishes (Rhamdia guatemalensis) for the first time. The larvae are briefly described and illustrated and problems concerning their morphology, taxonomy, hosts and geographical distribution are discussed. Adults of these larvae are parasitic in piscivorous fishes, reptiles, birds and mammals (definitive hosts). Fishes harbouring the larvae of these parasites serve as paratenic hosts, being mostly an important source of infection for the definitive hosts.
Keywords: Mexiko; Animals; Nematoda; Larva; zvířata; hlístice; Fishes; Mexico; larva; ryby